2021
DOI: 10.1111/crj.13428
|View full text |Cite
|
Sign up to set email alerts
|

Turkish language validity and reliability of the Control of Allergic Rhinitis and Asthma Test and its comparison with other scales

Abstract: Objectives Patients with asthma often suffer from concomitant allergic rhinitis (AR). The Control of Allergic Rhinitis and Asthma Test (CARAT) is a validated tool to assess asthma and rhinitis multimorbidity. Turkish language validity and reliability of CARAT and its compatibility with other scales were evaluated in the study. Methods Patients with asthma and concomitant AR were tested with CARAT. Pulmonary function tests, Asthma Control Test (ACT), Assessment Tool for Asthma (ATA) questionnaire and visual ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(24 citation statements)
references
References 29 publications
(41 reference statements)
0
24
0
Order By: Relevance
“…Construct (convergent) validity was assessed in 14 studies (published in 20 reports), 18–22,35–46,48–50 but one of them did not report correlation coefficients nor areas under the ROC curve 45 . For CARAT, 12 studies out of 13 studies (92%) showed ‘sufficient’ evidence for construct validity 18–22,35–40,42–44,46,48–50 . Eight studies assessed the construct validity for the CARAT subscales 18–22,35–39,48–50 and ‘sufficient’ evidence for construct validity was found in 6 (75%) studies for the upper airway subscale, 18,20–22,35,38,48–50 and 7 (87.5%) studies for the lower airway subscale 18,20–22,35–38,48–50 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Construct (convergent) validity was assessed in 14 studies (published in 20 reports), 18–22,35–46,48–50 but one of them did not report correlation coefficients nor areas under the ROC curve 45 . For CARAT, 12 studies out of 13 studies (92%) showed ‘sufficient’ evidence for construct validity 18–22,35–40,42–44,46,48–50 . Eight studies assessed the construct validity for the CARAT subscales 18–22,35–39,48–50 and ‘sufficient’ evidence for construct validity was found in 6 (75%) studies for the upper airway subscale, 18,20–22,35,38,48–50 and 7 (87.5%) studies for the lower airway subscale 18,20–22,35–38,48–50 …”
Section: Resultsmentioning
confidence: 99%
“…We included 16 original studies (published throughout 23 reports) in our systematic review (Table 1). 17–22,34–50 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations